2008
DOI: 10.1111/j.1540-5907.2008.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Interest: The Effects of Money on Citizen Participation in State Supreme Court Elections

Abstract: In this article, we investigate one highly significant aspect of the role of money in judicial elections: whether campaign spending increases citizen participation in the recruitment and retention of judges. Specifically, by using a two-stage modeling strategy that allows us to separate the effects of challengers from the effects of money, we assess whether relatively expensive campaigns improve the chances that citizens will vote in the 260 supreme court elections held from 1990 through 2004 in 18 states usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 40 publications
(76 reference statements)
5
94
1
Order By: Relevance
“…Spending by candidates and special interest groups in all states with judicial elections dramatically increased in recent years (Bonneau, 2005;Hall & Bonneau, 2009). A positive correlation has also been found between spending on judicial campaigns and citizen participation rates in state supreme court elections regardless of whether the balloting was partisan or non-partisan (Hall & Bonneau 2008). It should also be noted that research has identified a correlation between campaign contributions and judicial decisions in Texas courts, with judges voting conservatively on landmark cases and in cases in the months prior to an election (McCall & McCall, 2007).…”
Section: Judicial Elections: An Overview and Discussion Of Important mentioning
confidence: 99%
“…Spending by candidates and special interest groups in all states with judicial elections dramatically increased in recent years (Bonneau, 2005;Hall & Bonneau, 2009). A positive correlation has also been found between spending on judicial campaigns and citizen participation rates in state supreme court elections regardless of whether the balloting was partisan or non-partisan (Hall & Bonneau 2008). It should also be noted that research has identified a correlation between campaign contributions and judicial decisions in Texas courts, with judges voting conservatively on landmark cases and in cases in the months prior to an election (McCall & McCall, 2007).…”
Section: Judicial Elections: An Overview and Discussion Of Important mentioning
confidence: 99%
“…As empirical research has demonstrated, voter apathy is not inherent in state supreme court elections (e.g., Baum and Klein 2007;Hall 2007b;Hall and Bonneau 2008). Instead, citizen participation is driven primarily by factors that increase the salience of these races and provide information to voters (Baum and Klein 2007;Hall 2007b;Hojnacki and Baum 1992).…”
Section: Empirical Studies Of State Supreme Court Electionsmentioning
confidence: 99%
“…Instead, citizen participation is driven primarily by factors that increase the salience of these races and provide information to voters (Baum and Klein 2007;Hall 2007b;Hojnacki and Baum 1992). Particularly effective as mobilizing agents are partisan elections, quality challengers, tight margins of victory, and big spending (Baum and Klein 2007;Hall 2007b;Hall and Bonneau 2008).…”
Section: Empirical Studies Of State Supreme Court Electionsmentioning
confidence: 99%
“…The 2004 and 2008 elections saw especially increased expenditures per voter accompanied by a noticable increase in voter turnout. Given the relationship between campaign spending and turnout, campaigns are well advised to spend money on mobilizing voters (Baek 2009;Hall and Bonneau 2008). However, as campaigns increasingly face limited resources and budget constraints (in addition to public sentiment against excessive spending during times of economic hardship), it is important to allocate resources as efficiently as possible.…”
Section: Campaigning Mobilization and Turnout In The United Statesmentioning
confidence: 99%